Christmas vacation [videorecording (DVD)] - Chechik, Jeremiah; Chase, Chevy; D'Angelo, Beverly; Quaid, Randy, 1950-; Ladd, Diane; Randolph, John, 1915-2004; Marshall, E. G., 1914-1998; Roberts, Doris, 1925-2016; Louis-Dreyfus, Julia (Warner Home Video, 2003)
Christmas is the perfect season for Clark Griswold and his family. Clark's a disaster waiting to happen. You have to see it to believe it. There are 25,000 lights on the Griswold rooftop. An exploding turkey. And a house full of relatives.